A phase II study of a modified hyper-CVAD frontline therapy for patients with adverse risk diffuse large B-cell and peripheral T-cell non-Hodgkin lymphoma. Issue 4 (21st March 2019) - Hapgood, Greg; Stone, Janey M.; Zannino, Diana; George, Anup; Marlton, Paula; Prince, Henry Miles; Hui, Chi-Hung; Prosser, Ian; Lewis, Ian D.; Bradstock, Kenneth; Seymour, John F.; ,
Abstract: To improve complete remission (CR) rates by reducing toxicity and enhancing delivery, we created a modified hyper-CVAD/MA regimen (cyclophosphamide, vincristine, doxorubicin, dexamethasone/methotrexate, cytarabine) by reducing the cytarabine dose (3 g/m 2 to 2 g/m 2 ) and number of cycles (eight to six). We conducted a phase II trial in the pre-rituximab era in the intermediate–high international prognostic index (IPI) (≥2) de novo diffuse large B-cell lymphoma (DLBCL) and peripheral T-cell lymphoma (PTCL) (ACTRN12605000105640). CR rates were compared with reported IPI-stratified rates. Sixty-three patients ( n  = 26 PTCL; n  = 37 DLBCL) were evaluated; median follow-up of 30 months. CR rates for PTCL and DLBCL patients were 46% and 49%, respectively, similar with reported CR rates with CHOP-like chemotherapy ( p  = .6). Of the patients, 51 (81%) experienced ≥1 unplanned hospital admission; only 41 (65%) completed six cycles. The cytarabine modifications did not prevent significant toxicity. Modified hyper-CVAD/MA resulted in similar outcomes to CHOP-like chemotherapy in aggressive lymphomas and was associated with significant toxicity.